(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2019)
Background: Surgical management of vesico-vaginal fistula is very crucial regarding the outcomes among the women. Objectives: The purpose of the present study was to see the surgical outcomes of vesico-vaginal fistula. Methodology: This cross-sectional study was carried out from July 2013 to December 2013 for a period of 6 months in the National Fistula Centre in the Department of Obstetrics & Gynaecology at Dhaka Medical College Hospital (DMCH), Dhaka, Bangladesh. All patients who underwent surgical repair for iatrogenic VVF in National Fistula Centre of the department of Obstetrics and Gynaecology of Dhaka Medical College Hospital were included in this study. Patients who got themselves admitted to Obstetrics & Gynaecology department of DMCH with the complaints of fistula. An interview usually lasted for an hour. The entire selected patients were interviewed for detailed history. Thorough physical examination was done. The surgical outcomes were recorded among the women. Result: A total number of 51 cases of VVF were recruited for this study. The mean age was 46.02 (±SD 6.104) years. Regarding the causes of iatrogenic vesico-vaginal fistula most of the cases (88.2%) were abdominal hysterectomy. In 4(7.8%) patients lower segment caesarean section caused the situation. Vaginal hysterectomy was responsible for 3.9% (2/51) cases of iatrogenic VVF. In more than 90% cases (46/51) the surgical outcome was successful; while in 5 patients’ fistula recurred 5 to 7 days following surgery. They were treated by re-operation later on. Conclusion: In conclusion abdominal hysterectomy is the most common cause of iatrogenic vesico-vaginal fistula with a very good surgical outcomes. Journal of National Institute of Neurosciences Bangladesh, 2019;5(1): 29-32